COMPARATIVE ANALYSIS OF STOCK PORTFOLIO RISK & RETURN”WITH SINGLE INDEX METHOD - Pandin, Maria Yovita R (Universitas 17 Agustus 1945 Surabaya, 2023)
This study aims to compare the return and risk of investment in blue chip stocks (first liner) and second liner stocks of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2022 period. The method used is qualitative with single index theory, and closing price data is used for analysis. The results show that a portfolio of second liner stocks provides higher expected returns and lower risk compared to first liner stocks. Nonetheless. This research provides insights for investors and the public about the investment alternatives of first liner and second liner stocks, and shows the importance of portfolio diversification in managing investment risk. Future research can expand the scope of industry sectors and other analytical methods to explore a deeper understanding of stock investment on the IDX.